Can integrated agriculture-nutrition programs change gender norms on land and asset ownership? Evidence from Burkina Faso - van den Bold, Mara; Pedehombga, Abdoulaye; Ouédraogo, Marcellin; Quisumbing, Agnes R.; Olney, Deanna K. (International Food Policy Research Institute, 2013)
There is a high degree of interest in the potential for agricultural programs to be designed and implemented to achieve health and nutrition objectives. Policymakers have often looked to the experience of civil society organizations in designing and implementing such programs, particularly in different social and cultural contexts. For the past 20 years, Helen Keller International (HKI) has implemented homestead food production programs in Asia and recently has started to adapt and implement these programs in Africa south of the Sahara. The goal of these programs is to improve the nutritional status of and young children through a number of production and nutrition interventions. These interventions are targeted to mothers under the presumption that increasing women’s access to and control over productive assets and enhancing women’s human capital to improve production and health and nutrition care practices will translate into improved nutritional status for their children. However, there is very little evidence documenting the ways in which HKI’s homestead food production programs influence women’s access to and control over productive assets and enhance women’s human capital in ways that may improve nutritional outcomes. This paper uses a mixed-methods approach to analyze the impact of HKI’s Enhanced-Homestead Food Production pilot program in Burkina Faso on women’s and men’s assets and on norms regarding ownership, use, and control of those assets. Even though men continue to own and control most land and specific assets in the study area, women’s control over and ownership of assets has started to change, both in terms of quantifiable changes as well as changes in people’s perceptions and opinions about who can own and control certain assets. The paper also discusses the implications of such changes for program sustainability.